2012
DOI: 10.1002/glia.22296
|View full text |Cite
|
Sign up to set email alerts
|

Microglia are required for astroglial toll‐like receptor 4 response and for optimal TLR2 and TLR3 response

Abstract: Within the central nervous system, astrocytes and microglia are the primary responders to endogenous ligands released upon injury and stress, as well as to infectious pathogens. Toll-like receptors (TLRs) are implicated in recognition of both types of stimulus. Whether astrocytes respond as strongly as microglia to TLR agonists remains contentious. In this study, we have rigorously purified astrocytes to determine their capacity for autonomous TLR response, in absence of microglia. We used flow cytometry and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 50 publications
4
97
0
8
Order By: Relevance
“…Despite low accessibility of exo-or endogen- reported that TLR4 is barely expressed and was incapable of mediating cellular activation in human astrocytes (7,8,16,17). In contrast, other data have shown that human astrocytes respond to LPS challenge (6,18,19), suggesting that human astrocytes may possess functional TLR4-LPS receptor complex and participate in innate immune response by signaling through interaction between TLR4 and its ligand,…”
Section: Introductionmentioning
confidence: 99%
“…Despite low accessibility of exo-or endogen- reported that TLR4 is barely expressed and was incapable of mediating cellular activation in human astrocytes (7,8,16,17). In contrast, other data have shown that human astrocytes respond to LPS challenge (6,18,19), suggesting that human astrocytes may possess functional TLR4-LPS receptor complex and participate in innate immune response by signaling through interaction between TLR4 and its ligand,…”
Section: Introductionmentioning
confidence: 99%
“…Glial cells, e.g., astrocytes and microglia, are key regulators of the innate immune response in the CNS. These cells are the primary responders to cellular stress and infection, which cause them to induce, produce, and release molecular signals that initiate glial responses, leading to inflammation, neurodegeneration, and apoptosis (4). Microglia cells are classified as specialized macrophages of the CNS because they release proinflammatory cytokines and chemokines.…”
mentioning
confidence: 99%
“…They found that the CD4/CD8 lymphocyte ratio in vitreous is higher compared to the blood ratio in these PDR patients, demonstrating the presence of a local inflammatory process [7]. Prolonged local inflammation in hyperglycemic conditions in the retina may develop into a chronic inflammatory response that is detrimental to the integrity of BRB [6,[8][9][10]. The destruction of the barrier shifts the retina from its "privileged state" when the BRB functions normally to "compromised state" when the BRB has broken down.…”
Section: The Immune System In Proliferative Diabetic Retinopathymentioning
confidence: 93%
“…Their role in the pathogenesis of PDR is still under investigation but evidence suggests the possibility of a rather direct contribution. IL-6 controls immune cells responses by shifting T-helper cell populations, inhibiting the production of Th1 cells, promoting the differentiation of Th2 and Th17 cells, and infiltration of monocytes and T cells [9,10,83].…”
Section: Interleukinmentioning
confidence: 99%